Correlation between the cephalometric measurements and acoustic properties of /s/ sound in Turkish - Guzin Bilgin BUYUKNACAR; Aysegül GULEC (University of São Paulo, 2020)
Abstract Objectives To evaluate the acoustic properties of the /s/ sound in individuals with different occlusion types and to investigate relationships between these properties and cephalometric measurements. Methodology Sixty patients were divided into three groups based on malocclusion. Group 1 included 20 patients (mean age: 14.85±2.01 years) with Class I skeletal and dental relationships. Group 2 included 20 patients (mean age: 13.49±1.78 years) with Class II skeletal and dental relationships. Group 3 included 20 patients (mean age: 12.46±2.62 years) with Class III skeletal and dental relationships. Cephalometric tracings were obtained from cephalometric radiographs. All included patients were native speakers of Turkish. The /s/ sound was selected for center of gravity analysis. Correlations between cephalometric values and acoustic parameters were also investigated. Results The center of gravity of the /s/ sound had the lowest value in Group 2 (p<0.05). For the /s/ sound in Group 3, moderate positive correlations were found between center of gravity and Sella-Nasion to Gonion-Gnathion angle (p<0.05, r=0.444) Lower incisor to Nasion-B point (p<0.023, r=0.505), and Lower incisor to Nasion-B point angle (p<0.034; r=0.476). No correlation was found in other cephalometric measurements. Conclusions The /s/ sound was affected by malocclusion due to the changing place of articulation. Therefore, referral to an orthodontist for malocclusion treatment especially patients with class III in the early period is suggested for producing acoustically ideal sound.